Isolated internal iliac artery aneurysm causing rectal necrosis due to compression early after endovascular repair: A case report. (2019) - Imagami, Toru; Takayama, Satoru; Hattori, Taku; Matsui, Ryohei; Kani, Hisanori; Tanaka, Akimitsu; Kurokawa, Satoshi
Highlights: Many advantages of endovascular repair for aneurysms have been reported. The compression by aneurysms was not resolved early after endovascular repair. Rectal necrosis caused by residual aneurysms early after endovascular repair is rare. Aneurysm reduction and intestinal resection after embolization was a useful method. Embolization performed earlier assisted surgical decompression of aneurysms. Abstract: Introduction: Recently, endovascular repair has become the first-line treatment for internal iliac artery aneurysm (IIAA). However, rectal necrosis due to the compression of the residual IIAA early after endovascular repair is rare. Presentation of case: We present a rare case of a huge, isolated left IIAA that severely compressed the rectum and ureter. The patient underwent emergency endovascular repair; however, rectal necrosis occurred 10 days later because the repair failed to shrink the size of the aneurismal sac. Discussion: We hypothesize that the compression of the residual IIAA caused rectal necrosis. During open surgery, endovascular repair disrupted blood flow within the IIAA, which probably allowed for aneurysm dissection and residual hematoma removal. Conclusion: Endovascular repair alone could not immediately release compression on the surrounding organs; however, open surgical removal of aneurysms after successful endovascular repair may be a useful option for IIAAs with compression of surrounding organs.